2014
DOI: 10.1097/pas.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Dehydrogenase (SDH)-deficient Renal Carcinoma

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
149
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(159 citation statements)
references
References 43 publications
4
149
0
6
Order By: Relevance
“…Collectively, these changes are thought to drive tumorigenesis in the multiple organ systems that demonstrate increased incidence of neoplasia in individuals harboring germline SDHx mutations, which include paragangliomas/pheochromocytomas, GISTs and, among a subset, a histologically distinctive type of renal cell carcinoma (Gill et al 2014, Williamson et al 2015. Importantly, with regard to GISTs, SDH-deficient GISTs can be due to either genetic (SDHA, B, C or D mutations) or epigenetic (SDHC promoter methylation) changes.…”
Section: Sdh-deficient Gists (Sdha B C D Mutations Sdhc Epimutants)mentioning
confidence: 99%
“…Collectively, these changes are thought to drive tumorigenesis in the multiple organ systems that demonstrate increased incidence of neoplasia in individuals harboring germline SDHx mutations, which include paragangliomas/pheochromocytomas, GISTs and, among a subset, a histologically distinctive type of renal cell carcinoma (Gill et al 2014, Williamson et al 2015. Importantly, with regard to GISTs, SDH-deficient GISTs can be due to either genetic (SDHA, B, C or D mutations) or epigenetic (SDHC promoter methylation) changes.…”
Section: Sdh-deficient Gists (Sdha B C D Mutations Sdhc Epimutants)mentioning
confidence: 99%
“…SDH-deficient RCC has been recognized as novel entity in the 2016 WHO classification of renal tumors (44,45). It may show a morphologic spectrum wider than has been previously described (46) and some cases may be essentially indistinguishable from other non-SDH-related RCCs at histology.…”
Section: Renal Cell Carcinomas (Rccs)mentioning
confidence: 98%
“…In a more recent paper, Gill et al evaluated the morphology of 36 SDH-deficient RCCs from 27 patients and concluded that the most distinctive histologic feature was the presence of cytoplasmic vacuoles and inclusionlike spaces containing either pale eosinophilic fluid or flocculent material (42). Nonetheless, in some cases, these inclusions were focal and not easy to identify.…”
Section: Renal Cell Carcinomas (Rccs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nextgeneration sequencing of DNA extracted from paraffinembedded tissue showed an SDHB mutation and loss of the second in 5 of 6 tumors studied. A recent report by Gill et al 54 described 36 cases of succinate dehydrogenase-deficient RCCs, 21 of which were previously unreported. This study demonstrated the presence of the described morphologic features in 94% of the tumors studied and estimated that 0.05% to 0.2% of all RCCs are SDH deficient with a slight male predominance, bilaterality in 26%, and a strong association between high-grade nuclei and subsequent metastasis.…”
mentioning
confidence: 99%